Oracle Primavera P6 PPM Professional Advanced Features - Harris, Paul (Packt Publishing, 2021)
Primavera P6 Version 8 to Version 20, this module explains the differences between the versions About This Video Workshop on WBS (Work Breakdown Structure), LOEs (Level of Effort), and setting the baseline Workshop working on codes and User Defined Fields (UDF) Workshop on Global Change feature In Detail Primavera is an enterprise project portfolio management software. It includes project management, scheduling, risk analysis, opportunity management, resource management, and collaboration and control capabilities, and integrates with other enterprise software such as Oracle and SAP's ERP systems. This course aims to teach students the advanced features of Oracle Primavera Project Manager P6 PPM Professional tool. You will start with exploring scheduling options and setting a baseline for the project. Then you will move to understand user preferences and admin preferences and explore other methods of organizing project data in Primavera. You will also look at managing the Enterprise environment of Primavera. The exciting features like "global change" and how to schedule multiple projects will help you a lot in managing your project smoothly. Finally, you will look at the utilities part of the Primavera tool in detail. By the end of the course, you will successfully learn the advanced features of Primavera Project Manager P6 PPM Professional tool.
Online resource; Title from title screen (viewed June 25, 2021)
Keywords: Streaming video; Internet videos; Vidéo en continu; Vidéos sur Internet; streaming video; Electronic videos